Urgensi Pembentukan Laporan Khusus Sebagai Solusi Alat Bukti Surat Dalam Penanganan Kasus TPPU Di Indonesia: Pintu Optimalisasi Hubungan PPATK-Penyidik - Geraldine, Amanda; Altuti, Altuti; Firmansyah, Muhamad Rayhan (Jurnal Hukum & Pembangunan, 2022)
The Financial Transaction Reports and Analysis Centre or Financial intelligence unit (FIU) is an independent institution that has helped to eradicate and prevent money laundering crimes based on reports used as evidence or evidence in investigations. PPATK analysis report is made based on the report of the income and expenditure of unusual financial accounts by referring to the profile and identity of the owner. Financial Transactions requested by PPATK to be reported by the reporting party because it involves assets suspected of originating from the proceeds of a criminal offence. FATF has issued 40 specific recommendations (forty recommendations) and the eradication of money laundering, which are expected to be used by each country and 8 specific recommendations to combat the financing of terrorism. PPATK has the right to analyse assets from information provided by financial service providers. Therefore, there must be a result of PPATK's analysis as evidence, namely by introducing new products resulting from the coordination relationship between PPATK and the investigators.